Store environment: The value of insignia - Marques, S.; Salgueiro, M. F. (Eirass 2008, 2008)
In order to analyse store choice criteria, it is required to consider the environment of the store (Baker et al., 2002). The ambient, the design of the store and the personal service are the factors under analysis since they are considered the most relevant ones (Baker et al., 1992). This paper uses Confirmatory Factor Analysis (CFA) to test a store environment measurement model (16 hypermarkets in the Lisbon Metropolitan Area). A multiple group CFA is used to study the influence of the insignia on store environment. When analysing the environment of a store there are three factors that can affect choice criteria: the design, the ambient and the personal service. This paper investigates a conceptual model with three latent constructs: Store Ambient Perceptions, Store Design Perceptions and Personal Service Perceptions. These three latent variables are measured by the following manifest indicators: Store Ambient, Organized Merchandise, Store Architecture, Store Design, Store Decoration, Customers Treated Well, Quality Service Store and Personal Attention. Each indicator corresponds to an item of a structured questionnaire used in personal interview, measured on a seven point Lickert type scale from 1=“strongly disagree” to 7=“strongly agree”. Data for this study were collected under a complex sampling design: all the 16 hypermarkets in the Lisbon Metropolitan Area were considered, representing four insignias: Auchan, Continente, Carrefour and Feira Nova. Since it is not possible to obtain a list of all the customers of a given hypermarket, non-random samples were selected in each hypermarket. Samples are proportional to the size of the population, over 18 years old, living in the area of the hypermarket. Different days of the week and hours of the day were considered. Interviews were based on structured questionnaires accomplished at the checkout exit. The final sample size equals 561 customers. The fit of the model is considered satisfactory: Satorra-Bentler scaled Chi-Square = 26.54; df = 17; p-value = 0.065; RMSEA = 0.032; RMR = 0.04; GFI = 0.98 and NFI = 0.99. To assess the discriminating validity of the three constructs, the average variance extracted (AVE) of each construct was calculated and compared to the shared variance of all possible pairs of constructs. AVE values range from 78% to 82%, indicating discriminating validity among the constructs. Reliability was assessed by calculating the composite reliability of each scale. Obtained values ranging from 0.76 to 0.93 suggest that each scale has good reliability. The distribution of the 561 interviewees by insignia is the following: Auchan (100), Continente (134), Carrefour (124) and Feira Nova (203). A multiple group CFA was used, aiming at testing the invariance of both factor loadings and correlations between store environment perceptions, for the four groups of insignia customers. The null hypothesis of invariance of the factor loadings in the four groups is not rejected (∆?2 = 14.23 e ∆ df = 15), whereas the null hypothesis of invariance of the correlation structure between latent variables is rejected (∆?2 = 17.24 e ∆ df = 9). In summary, we examine the influence of insignia in store environment and propose a framework that helps in understanding and predicting these relationships. The main contribution of this paper is presenting a conceptual model for store environment that includes three correlated constructs: Ambient Store Perceptions, Design Store Perceptions and Personal Service. Confirmatory Factor Analysis is used to test the proposed model, based on a sample of 561 customers of hypermarkets in Lisbon Metropolitan Area. The influence of the insignia on the store environment is assessed by using a multiple group CFA. The paper focuses on hypermarket customers, thus excluding other types of stores. As in most applied studies involving consumer behaviour, the fact that the sample unit is the hypermarket customer does not allow for random sampling, with all underlying limitations regarding statistical inference.